2019
DOI: 10.3758/s13428-019-01259-5
|View full text |Cite
|
Sign up to set email alerts
|

Privacy versus open science

Abstract: Pervasive internet and sensor technologies promise to revolutionize psychological science. However, the data collected using these technologies are often very personal—indeed, the value of the data is often directly related to how personal they are. At the same time, driven by the replication crisis, there is a sustained push to publish data to open repositories. These movements are in fundamental conflict. In this article, we propose a way to navigate this issue. We argue that there are significant advantages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 24 publications
0
35
0
Order By: Relevance
“…For example, emailing a password to a researcher is only as secure as a researcher's email. On the other hand, additional security procedures could make the app more difficult to use and limit the adoption of open science practices (Dennis et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, emailing a password to a researcher is only as secure as a researcher's email. On the other hand, additional security procedures could make the app more difficult to use and limit the adoption of open science practices (Dennis et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…While we have encountered several papers [AA12, AAFJ16] focusing on privacy issues of spatial data, such research needs to be integrated more deeply with the research involving privacy‐preserving urban data collection [LA15, TAS*18] and decisionmaking. Research grounded in behavorial sciences that has recently demonstrated the benefits of using visualization‐based interfaces for granting citizens the transparency to directly administer and understand the implications of data sharing [DGY*19]. Visualization techniques need to be further developed and explored for more inclusive and transparent citizen science, where third party interference can be minimized and citizens can more proactively exercise their right to privacy.…”
Section: Gaps and Research Opportunitiesmentioning
confidence: 99%
“…This issue is complex and deserves a deeper analysis of the balance between risks and mitigations, but they are currently beyond the scope of the present work. There are, however, important strides being taken toward a coherent strategy to navigate these security and privacy matters (Dennis et al, 2019).…”
Section: Self-report Datamentioning
confidence: 99%